Dīwān-i Ghālib-i Dihlawī : Mushtamil bar ghazaliyyāt u rubāʿiyyāt-i Fārsi - Khān, Mīrzā Asadallāh, (Miras Maktoob, ISBN: 9789004365452., 2019)
Mīrzā Asadallāh Khān, better known by his pen-name of Ghālib Dihlawī, is the last one of the great poets of the Mughal era. Born in Agra in 1212/1797, he traced his origins back to Tūrān, his paternal grandfather having emigrated from Transoxania to India during the reign of Shāh ʿĀlam (r. 1759-1806). While mostly known as one of the foremost Urdu poets, Ghālib's Persian work, poetry and prose, is of comparable quality. In his childhood days, his Persian had been greatly improved thanks to the teachings of a Persian immigrant by the name of ʿAbd al-Ṣamad. But even if Ghālib acknowledged ʿAbd al-Ṣamad's qualities as a teacher and a human being, as a writer of Persian poetry, he regarded his talents as God-given. Ghālib's life was full of drama: an unhappy marriage, the loss of all his children, alcoholism, depression, and years of financial hardship. Plagued by ill health, he died in Delhi, aged 71.